Analysis of Differences in AI Literacy Levels among Students at SMPN 1 Purwakarta in IT Classes and Regular Classes - Sri Rahayu; Ulva Elviani (FKIP - Universitas Riau, 2026)
Artificial intelligence (AI) is increasingly integrated into learning, encompassing conceptual understanding, practical skills, ethics, and attitudes/motivation/self-efficacy. This study aimed to describe AI literacy levels among junior high school students in IT and regular classes and to analyze differences between both groups at SMPN 1 Purwakarta. A non-experimental quantitative approach with an ex post facto comparative design was employed involving 132 eighth-grade students (66 IT and 66 regular). Instrument quality was examined using Aiken’s V for content validity, corrected item–total correlation, and Cronbach’s alpha/KR-20 for reliability. Data were analyzed using descriptive statistics, Shapiro–Wilk normality test, and independent t-test or Mann–Whitney U test based on distribution. Results indicated a significant difference only in the AI Ethics indicator, with IT students scoring higher (M = 4.04, SD = 0.52) than regular students (M = 3.82, SD = 0.64; p = 0.027; g = 0.38). Other indicators (Apply/Use, Attitude/ Motivation/ Self-efficacy, total Likert score, and Understand) showed no significant differences (p > 0.05). These findings highlight the importance of strengthening AI ethics across classes and improving measurement of conceptual understanding in future research.